2021
DOI: 10.20961/stjssa.v18i1.47553
|View full text |Cite
|
Sign up to set email alerts
|

The comparison between conventional and rice ratoon system on soil properties, rice productivity and nutrient status

Abstract: <p>Ratoon system is a method of rice cultivation that produces new tillers after the mother plant is harvested and is continued by maintaining and caring for the shoots of the mother plant. In Indonesia, SALIBU and SINGGANG, which are types of rice ratooning, have been developed for Sumatra and Java regions, respectively. SALIBU is an innovation or a modification of the rice ratoon system that focuses on maintaining the time of fertigation and cutting of plant height. SINGGANG, on the other hand, is a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Minimum soil tillage significantly affected most rice growth and yield parameters as well as soil physical and chemical parameters, compared to notillage and maximum tillage. Sakti et al (2021) demonstrated that the ratoon rice cropping system (regrowing rice plants from the results of previous crop pruning, which significantly reduces soil tillage) improved rice growth and yield parameters as well as physical and chemical properties of the soil (it requires soil preparation first). The results of previous studies have described the impact of conventional tillage systems through puddle pores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimum soil tillage significantly affected most rice growth and yield parameters as well as soil physical and chemical parameters, compared to notillage and maximum tillage. Sakti et al (2021) demonstrated that the ratoon rice cropping system (regrowing rice plants from the results of previous crop pruning, which significantly reduces soil tillage) improved rice growth and yield parameters as well as physical and chemical properties of the soil (it requires soil preparation first). The results of previous studies have described the impact of conventional tillage systems through puddle pores.…”
Section: Resultsmentioning
confidence: 99%
“…Vertisol is the potential soil type due to its reasonably high land productivity (Wubie, 2015), even higher than Inceptisol and Alfisol (Sakti et al, 2021). The high value of CEC and having a pH value that tends to be neutral are positive characteristics of Vertisol, as shown by (Hamoud et al, 2019) that the increase in clay content in the soil is in line with the increase in K uptake in rice.…”
Section: Introductionmentioning
confidence: 99%
“…Almost 60 per cent of wetland rice farmers have implemented the Salibu rice technology and it is expected to increase in the following year. This is supported by the high attention of the district government through the agriculture office to programme Salibu rice farming as a mainstay in rice farming 13,15 . The local institution of Tuo Banda is expected to play a significant role in ensuring the availability of water in implementing Salibu rice farming technology.…”
Section: Introductionmentioning
confidence: 99%